Charity and giving in monotheistic religions - Frenkel, Miriam; Lev, Yaacov (Studien zur Geschichte und Kultur des islamischen Orients (2004), 2009)
This book deals with various manifestations of charity or giving in the contexts of the Christian, Jewish, and Muslim societies in Late Antiquity and Early Middle Ages. Monotheistic charity and giving display many common features. These underlying similarities reflect a commonly shared view about God and his relations to mankind and what humans owe to God and expect from him. Nevertheless, the fact that the emphasis is placed on similarities does not mean that the uniqueness of the concepts of charity and giving in the three monotheistic religions is denied. The contributors of the book deal w.